Relived memories - Jayewardene, Junius Richard; Jayewardene, Junius Richard (Colombo : J.R. Jayewardene Centre, 1996)
Collection of speeches of the former President of Sri Lanka.
Sequel to Men and memories : autobiographical recollections and reflections.
Includes index.
Published in New Delhi by Navrang, Booksellers & Publishers.